Global phylogeography and evolutionary history of Shigella dysenteriae type 1 - Njamkepo, Elisabeth; Fawal, Nizar; Tran-Dien, Alicia; Hawkey, Jane; Strockbine, Nancy; Jenkins, Claire; Talukder, Kaisar A; Bercion, Raymond; Kuleshov, Konstantin; Kolínská, Renáta; Russell, Julie E; Kaftyreva, Lidia; et al. (Nature microbiology, 2016)
Together with plague, smallpox and typhus, epidemics of dysentery have been a major scourge of human populations for centuries(1). A previous genomic study concluded that Shigella dysenteriae type 1 (Sd1), the epidemic dysentery bacillus, emerged and spread worldwide after the First World War, with no clear pattern of transmission(2). This is not consistent with the massive cyclic dysentery epidemics reported in Europe during the eighteenth and nineteenth centuries(1,3,4) and the first isolation of Sd1 in Japan in 1897(5). Here, we report a whole-genome analysis of 331 Sd1 isolates from around the world, collected between 1915 and 2011, providing us with unprecedented insight into the historical spread of this pathogen. We show here that Sd1 has existed since at least the eighteenth century and that it swept the globe at the end of the nineteenth century, diversifying into distinct lineages associated with the First World War, Second World War and various conflicts or natural disasters across Africa, Asia and Central America. We also provide a unique historical perspective on the evolution of antibiotic resistance over a 100-year period, beginning decades before the antibiotic era, and identify a prevalent multiple antibiotic-resistant lineage in South Asia that was transmitted in several waves to Africa, where it caused severe outbreaks of disease.
Keywords: séroskupina; Phylogeography; History, 20th Century; Global Health; celosvětové zdraví; lidé; Genome, Bacterial; Evolution, Molecular; molekulární evoluce; dějiny 20. století; bakteriální léková rezistence; genom bakteriální; Dysentery, Bacillary; Shigella dysenteriae; fylogeografie; Molecular Epidemiology; History, 19th Century; Sequence Analysis, DNA; History, 21st Century; bacilární dyzentérie; sekvenční analýza DNA; dějiny 19. století; Drug Resistance, Bacterial; dějiny 21. století; Serogroup; molekulární epidemiologie; Humans